Analisis Pelayanan Prima Terhadap Loyalitas Pelanggan Pada Hotel Megaria - Semuel Batlajery (Musamus Journal of Business & Management is a peer-reviewed journal published by Faculty of Ecconomics and Business, Musamus University, Merauke Papua Indonesia., 2019)
The purpose of this research is to know the Service Excellence analysis of customer loyalty at Hotel Megaria Merauke. Methods: Quantitative approaches, data sources: primary data and secondary data, data collection techniques: observations, interviews and questionnaires. Population and samples: numbering 40 respondents using total sampling and data analysis techniques: simple linear regression assisted by SPSS. The results of this study showed a regression coefficient of X of 0.254 meaning that excellent service variables have a positive and significant influence on customer loyalty which means that the service affects customer loyalty in Hotel Megaria Merauke.